Premium Differentiation in the Unemployment Insurance System and the Demand for Labor - Rob J.M. Alessie; Hans Bloemen (Tinbergen Institute, 2000)
We simulate the effect of the introduction of premium differentiation (experience rating) in the Dutch Unemployment Insurance system on the demand for labor for a variety of sectors in the Dutch economy. For the simulations we use the Bentolila and Bertola (1990) framework as a point of departure. In the simulations, the introduction of experience rating is modeled as expenditure neutral: in the absence of premium differentiation the cost of financing UI is modeled as a wage tax (independent of the number of workers fired by the firm), whereas in the presence of experience rating this cost is attributed to firing cost (affected by the firing action). Thus, the introduction of experience rating results in a shift from wage cost to firing cost. Following the political debate on the issue in the Netherlands, we assume that the introduction of experience rating does neither lead to a change in tax rates paid by workers nor to a change in eligibility rules or replacement rates of benefit claimants. Specific attention is paid to the distinction between `young' and `old' workers . In the model, labor adjustment costs (hiring and firing costs) are linear. The model allows for uncertainty in the business cycle.
Keywords: J20; J60; J65; 330; Unemployment Insurance; premium differentiation; labor demand; Arbeitslosenversicherung; Versicherungsbeitrag; Arbeitsuche; Niederlande